Survival of Immobilized Probiotics After Freeze-Thawing in Modified Gels of Sodium Alginate - Buriak, Iryna A.; Abrafikova, Liliia G.; Pishko, Olga V.; Babinets, Olga M. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):172.